REFLECTIONS OF CHANGES IN AGRICULTURE AND FOOD PRICES TO HOUSEHOLD AND PRODUCERS: ALTERNATIVE FISCAL POLICIES IN THE FRAMEWORK OF SOCIAL ACCOUNTING MATRIX (Third Sector Social Economic Review, 2019)
The hikes of agriculture and food price negatively affect households, especially unemployed people. This study examines the impact of agricultural prices on different social segment in the frame work of Micro-Social Accounting Matrix (SAM) with various economic and financial scenarios and compares alternative fiscal policy scenarios. Within the scope of this analysis, the effects of and external shock that may raise in agriculture and food prices on commodity markets, labor markets and households can be followed simultaneously. As a result, it is seen that price shocks mostly affects small producer and the poorest segments of households. In order  to compensate for the negative impacts, It was calculated that the income subsides that households directly benefited from more useful than agricultural input supports. It has been observed that the negative impacts caused by the prices shocks have not disappeared with the producer supports and even the producers have benefited from the increasing prices.
Keywords: Agriculture and Food Price Shocks; Micro-Social Accounting Matrix; Price Multiplier Analysis; Alternative Fiscal Policy; Food Crisis